Organ-Specific Gene Expression Reveals the Role of the Cymbidium ensifolium-miR396/Growth-Regulating Factors Module in Flower Development of the Orchid Plant Cymbidium ensifolium - Yang, Fengxi; Lu, Chuqiao; Wei, Yonglu; Wu, Jieqiu; Ren, Rui; Gao, Jie; Ahmad, Sagheer; Jin, Jianpeng; Xv, Yechun; Liang, Gang; Zhu, Genfa (Frontiers in Plant Science, 2022)
Orchids are some of the most popular ornamental plants worldwide. Orchid floral morphology has increasingly attracted horticultural and commercial attention. Although multiple genes have been shown to be involved in the formation of the orchid flower, the underlying multi-level regulatory networks are largely unknown. In this study, we analyzed the ontogeny of flower development in Cymbidium ensifolium, a traditional orchid in the tropical and subtropical regions of Asia, by performing deep sequencing of the transcriptome of individual flower organs to discover organ-specific genes potentially involved in their growth. We identified 3,017 differentially-expressed genes (DEGs) during the development of various flower organs, and observed over-representation of GROWTH-REGULATING FACTORS (GRFs) specific to flower column (gynostemium). Eleven C. ensifolium GRFs (CeGRFs) from our transcriptome data clustered into five phylogenetic subgroups. Ten of these GRFs shared a region complementary to C. ensifolium microRNA396 (Ce-miR396), and degradome sequencing confirmed the cleavage of transcripts derived from seven CeGRFs. We cloned Ce-miR396 and used a protoplast-based transient expression system (PTES) to overexpress it in Cymbidium protoplasts. We observed a significant decrease in the transcripts of several CeGRFs in flowers and leaves, indicating a potential role for miR396–GRF module in organ development through the cleavage of distinct CeGRFs. Temporal and spatial expression analysis indicated that most CeGRF transcripts accumulated in flower buds and column tissues, where Ce-miR396 expression was the lowest. Expression dynamics in wild type and floral-defective mutants further confirmed a strong correlation between Ce-miR396, CeGRFs, and flower organ development and column specification. Moreover, overexpression of Ce-miR396 in Nicotiana tabacum resulted in curved pistils and reduced fertility, implying that the conserved role of Ce-miR396 in floral development. These results provide tools to better understand the biological roles of GRFs in orchid development, and open new avenues for the diversification of orchid floral patterns.